2006
DOI: 10.1021/ja057967t
|View full text |Cite
|
Sign up to set email alerts
|

Four-Membered Group 13 Metal(I) N-Heterocyclic Carbene Analogues:  Synthesis, Characterization, and Theoretical Studies

Abstract: The synthesis, spectroscopic and structural characterization of the monomeric, four-membered group 13 metal(I) heterocycles ([:M{eta2-N,N'-(Ar)NC(NCy2)N(Ar)}], M = Ga or In, Ar = C6H3Pri2-2,6) and an isomeric thallium complex are reported. Theoretical studies on these complexes, which are analogues of four-membered N-heterocyclic carbenes, suggest they should act as good sigma-donor ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
144
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 15 publications
7
144
1
4
Order By: Relevance
“…The early compounds were stabilized by g 5 -C 5 Me 5 and C(SiMe 3 ) 3 substituents. Later, the range of available examples was further expanded with use of terphenyl [4][5][6] and b-diketiminate and related ligands [7][8][9][10][11]. The ability of these low-valent metal (I) compounds to act as strong terminal or bridging r-donor ligands has been well demonstrated by the experimental studies of Fischer, Jutzi and Uhl and by the theoretical work of Frenking [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The early compounds were stabilized by g 5 -C 5 Me 5 and C(SiMe 3 ) 3 substituents. Later, the range of available examples was further expanded with use of terphenyl [4][5][6] and b-diketiminate and related ligands [7][8][9][10][11]. The ability of these low-valent metal (I) compounds to act as strong terminal or bridging r-donor ligands has been well demonstrated by the experimental studies of Fischer, Jutzi and Uhl and by the theoretical work of Frenking [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although monomeric one-coordinate metal(I) structures are known from indium and thallium in the solid state, as in [:InAr*] [40] and [TlAr*], [41] it is rare for Ga(I). To date, the only example of a one-coordinate Ga(I) species in the solid state is the amide [:GaNA C H T U N G T R E N N U N G (SiMe 3 )C 6 H 3 -2,6-Mes 2 ] [42] in which, presumably, the more electronegative amide ligand increases the HOMO-LUMO gap to the extent that a metal-metal interaction is greatly weakened (related, monomeric, two-coordinate, N-bonded [:Ga{NA C H T U N G T R E N N U N G (Dipp)CMe} 2 CH] [43] and [:Ga{NA C H T U N G T R E N N U N G (Dipp)} 2 CNCy 2 ] [44] have also been reported). An electron diffraction study of [:Ga{CA C H T U N G T R E N N U N G (SiMe 3 ) 3 }] has shown that it is a monomer in the vapor phase [45] although it is tetrameric in the solid state with a tetrahedral arrangement of galliums.…”
mentioning
confidence: 99%
“…[1, [3][4][5][6][7] Die s-Donorund p-Acceptoreigenschaften dieser Liganden wurden ausführlich diskutiert (Abbildung 1) und lösten in manchen Fällen nicht wenige Kontroversen aus. [8][9][10] Solche Eigenschaften hängen stark von der Art des Diylsubstituenten R ab; so ist Cp*Ga ein sehr guter sDonor-Ligand, fungiert aber wegen der stark konkurrierenden p-Donoreigenschaften des Cp*-Fragments als schwacher p-Acceptor gegenüber Über-gangsmetallzentren.…”
unclassified